Design strategies for VR science and education games from an embodied cognition perspective: a literature-based meta-analysis - Lin, Xiuyu; Li, Runbo; Chen, Zhirong; Xiong, Jiayi (Frontiers in Psychology, 2024)
Introduction Natural science education, as an important means to improve the scientific literacy of citizens, combines science education games with virtual reality (VR) technology and is a major developmental direction in the field of gamified learning. Methods To investigate the impact of VR science education games on learning efficiency from the perspective of embodied cognition, this study uses the China National Knowledge Infrastructure (CNKI) and Web of Science (WOS) databases as the main source of samples. A meta-analysis of 40 studies was conducted to examine teaching content, game interaction, and immersion mode. Results The study found that (1) VR science and education games have a moderately positive impact on the overall learning effect; (2) regarding teaching content, the learning effect of skill training via VR science and education games is significant; (3) regarding interaction form, the learning effect on active interaction is significantly better than that of passive interaction; (4) regarding immersion mode, somatosensory VR games have a significant impact on the enhancement of students’ learning; (5) regarding application disciplines, VR science education games have a greater impact on science, engineering, language and other disciplines; (6) regarding academic segments, the learning effect on college students is most significant; and (7) regarding experimental intervention time, short-term intervention is most effective. Discussion Accordingly, this article proposes strategies for VR science game design from the perspective of embodied cognition: a five-phase strategy including skill training, human-computer interaction, and environmental immersion, aiming to improve the learning effect and experience of users.